Kinetic Modeling Study of Laminar Burning Velocity of Gasoline–Ethanol–Methanol Blends at Elevated Temperature and Pressure - Auzani, Ahmad Syihan; Wibowo, Cahyo Setyo; Anggarani, Riesta; Nugroho, Yulianto Sulistyo; Sugiarto, Bambang (Makara Journal of Technology, 2021)
Gasoline–ethanol–methanol (GEM) blends have been considered to replace pure gasoline as spark ignition engine fuel. Their physical and chemical properties and performance and emission measurements from real engines have been reported previously. However, a fundamental study that can explain the unique results of GEM compared with those of pure gasoline is lacking. This study aims to compare the laminar burning velocity of GEM blends at different mixtures, equivalence ratios, temperatures, and pressures with that of pure gasoline. A laminar flame propagation model and reaction mechanisms from the literature were were for a numerical simulation. In this study, the chemical components of real gasoline are simplified using a binary surrogate mixture. Results show that the laminar burning velocity of the GEM increased with the increase in temperature, ethanol, and methanol concentration, and it decreased with the increase in pressure. Sensitive reactions to laminar burning velocity are presented through a sensitivity analysis.